Research on the Application of Automatic Production Line Based on Computer Control Technology. Issue 2 (August 2021) - Li, Mingjun; Chen, Deming; Wu, Qing
Abstract: Information technology and computer technology in every field of society are playing a huge role, in the field of automatic production, computer technology with its strong operation and calculation ability and data processing ability, further promote the centralized control of automatic assembly line. In the future, it is an inevitable trend for computer system to replace human control. The application of computer technology can not only greatly improve the control efficiency, but also save manpower and material resources to a greater extent, and promote the progress of production level as a whole. Computer control technology is a computer-based technology. It is of great significance to analyze the application of computer control technology in automatic production line. Just as technology has changed our lives, it has also changed the way we produce and work. Nowadays, with the development of computer technology, network technology, information technology and other high and new technologies, all fields of the society have undergone earth-shaking changes, including the field of industrial production. Now the industrial production has realized the automatic assembly line production, and in order to better control the automatic assembly line production, in order to ensure its production efficiency, safety and stability, it must be applied to the computer control technology. At the same time, the application of computer control technology also helps to save human and material resources, thus saving the overall production cost and improving the economic efficiency of enterprises.